2013
DOI: 10.1038/cddis.2013.289
|View full text |Cite
|
Sign up to set email alerts
|

USP2a alters chemotherapeutic response by modulating redox

Abstract: Cancer cells are characterized by altered ubiquitination of many proteins. The ubiquitin-specific protease 2a (USP2a) is a deubiquitinating enzyme overexpressed in prostate adenocarcinomas, where it exhibits oncogenic behavior in a variety of ways including targeting c-Myc via the miR-34b/c cluster. Here we demonstrate that USP2a induces drug resistance in both immortalized and transformed prostate cells. Specifically, it confers resistance to typically pro-oxidant agents, such as cisplatin (CDDP) and doxorubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 58 publications
(91 reference statements)
1
22
0
Order By: Relevance
“…the expression of cyclins, a growing body of evidence has suggested that USP-2 plays an important role in modulation of development and treatment of cancer via a number of different ways. For example, USP-2 has been reported to prevent apoptosis in human prostate cancer (Priolo et al, 2006), confer drug resistance to prooxidant agents in cancer cells (Benassi et al, 2013), cause malignant transformation in human prostate epithelial cells (Stevenson et al, 2007), and augment tumorigenicity in an in vivo tumor assay (Hussain et al, 2009). As mentioned earlier, adiponectin and leptin have long been considered as endogenous hormones playing an important role in the modulation of cancer through diverse mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…the expression of cyclins, a growing body of evidence has suggested that USP-2 plays an important role in modulation of development and treatment of cancer via a number of different ways. For example, USP-2 has been reported to prevent apoptosis in human prostate cancer (Priolo et al, 2006), confer drug resistance to prooxidant agents in cancer cells (Benassi et al, 2013), cause malignant transformation in human prostate epithelial cells (Stevenson et al, 2007), and augment tumorigenicity in an in vivo tumor assay (Hussain et al, 2009). As mentioned earlier, adiponectin and leptin have long been considered as endogenous hormones playing an important role in the modulation of cancer through diverse mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…For example, certain chemotherapeutic agents, such as cisplatin, doxorubicin, or 2-methoxyestradiol, directly or indirectly modulate higher tumoral ROS production [7679], a process which is necessary for tumor death. Indeed, while tumors utilize ROS to their growth advantage, very high levels of ROS are cytotoxic and result in tumor cell death [80].…”
Section: Targeting Ros To Improve Cancer Therapymentioning
confidence: 99%
“…43 Fluorescence imaging analysis ( Figure 10B) exhibited that the nuclear morphology of cells treated with XNMs for 24 hours was almost the same as controls, whereas DNA fragmentation and/or chromatin condensation could be clearly observed in cells treated with DTX or DTX-loaded nanomicelles, indicating that the DTX could induce apoptosis in A2780 cells. 44 The number of cells treated with DTX or DTX-loaded nanomicelles was much lower than that of control group.…”
mentioning
confidence: 99%